Comparison of Urban-Rural Readmission Rates After Colorectal Cancer Surgery: Findings From a Privately Insured Population. (12th August 2021) - Alyabsi, Mesnad; Charlton, Mary; Meza, Jane; Islam, K. M. Monirul; Soliman, Amr; Watanabe-Galloway, Shinobu
Objectives: We assessed the 30-day readmission rate of a privately insured population diagnosed with colorectal cancer (CRC) who had primary tumor resection in rural and urban communities. Methods: Claims data of people aged <65 with a diagnosis of CRC between 2012 and 2016 and enrolled in a private health plan administered by BlueCross BlueShield of Nebraska were analyzed. Readmission was defined as the number of discharged patients who were readmitted within 30 days, divided by all discharged patients. Multivariate logistic regression was used to estimate the factors associated with readmission. Results: The urban population had a higher readmission rate (11%) than the rural population (8%). Although the adjusted odds ratio showed that there is no difference in readmission between rural and urban residents, patients with a Charlson Comorbidity Index (CCI) of >1 were more likely than those without CCI to be readmitted (OR 3.59, 1.41-9.11). Patients with open vs. laparoscopic surgery (OR 2.80, 1.39-5.63) and those with an obstructed or perforated colon vs. none (OR 7.17, 3.75-13.72) were more likely to be readmitted. Conclusions: Readmission after CRC surgery occurs frequently. Interventions that target the identified risk factors should reduce readmission rates in this privately insured population.